2021
DOI: 10.1186/s12955-021-01713-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of resilience with quality of life levels in adults experiencing homelessness and mental illness: a longitudinal study

Abstract: Background Homelessness constitutes a traumatic period that adversely impacts health and quality of life outcomes. The potential mitigating effects of resilience on quality of life levels in people experiencing homelessness are underresearched. This study assesses the longitudinal associations between resilience and quality of life scores among adults experiencing homelessness and mental illness. Methods This study is a secondary analysis of longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
4
15
0
1
Order By: Relevance
“…Thus, resilience is a valuable resource that can help patients with depression and other psychiatric conditions achieve therapeutic success (Devi et al., 2021 ; Zhang et al., 2020 ). Further supporting the findings of our study, stronger resilience was observed among homeless individuals with mental illnesses, and this was positively associated with QoL in terms of higher global mental health indicators (Mejia‐Lancheros et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, resilience is a valuable resource that can help patients with depression and other psychiatric conditions achieve therapeutic success (Devi et al., 2021 ; Zhang et al., 2020 ). Further supporting the findings of our study, stronger resilience was observed among homeless individuals with mental illnesses, and this was positively associated with QoL in terms of higher global mental health indicators (Mejia‐Lancheros et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The literature on resilience corroborates our findings, stating that the more stress a person is exposed to, or the longer they are exposed to it, the less resilient they become (Bozdağ & Ergün, 2021 ). In terms of QoL, the resilience of nursing faculty and students (Keener et al., 2021 ) as well as homeless adults with mental illness (Mejia‐Lancheros et al., 2021 ) is much higher. Accordingly, resilience is strongly linked to QoL (Zhang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is, therefore, a key component in trauma research [ 25 ] although there are discussions on the complex and multisystemic nature of resilience [ 24 , 26 ]. Individuals who are resilient are said to have better mental health profiles [ 24 , 27 ], including better quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…It therefore, is a multidimensional construct of health that goes beyond clinical diagnoses. Studies suggest that there is relationship between resilience and quality of life [ 27 ] but the nature of the relation between the two has not been studied extensively, especially in context of trauma and childhood trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Homelessness is widely considered as an individual [1][2][3], social [3][4][5][6], economic [7,8], and political [9] problem that affects the functioning of both individuals and whole of societies. Gu et al [10] report that more than 150 million people worldwide are homeless.…”
Section: Introductionmentioning
confidence: 99%